THE INFLUENCE OF COMPETENCY AND LEADERSHIP ON EMPLOYEE PERFORMANCE IN THE BUREAU OF FINANCIAL AND PUBLIC ADMINISTRATION OF GORONTALO STATE UNIVERSITY - Taha, Ratna Linda; Ilato, Rosman; Abdussamad, Zuchri (Public Policy Journal, 2020)
The objective of this research is to analyze the influence, either partial or simultaneous, of competency and leadership on employee performance in the bureau of financial and public administration of Gorontalo State University. The research approach was quantitative. The research method was ex post facto. The research design was causality. The data analysis technique was double regression. The findings indicate that (1) Employee competency had a positive significant influence on employee performance in the bureau of financial and public administration of Gorontalo State University at a coefficient of determination of 29.10%, (2) Leadership had a positive significant influence on employee performance in the bureau of financial and public administration of Gorontalo State University at a coefficient of determination of 22.30%, and (3) Employee competency and leadership had a simultaneous significant influence on employee performance in the bureau of financial and public administration of Gorontalo State University at a coefficient of determination of 51.40%. Others, i.e., 48.60%, could be elucidated by other variables unexplained in this research, e.g., work motivation, organizational culture, work climate, workload, and work supervision.